Effects of a financial incentive scheme for dementia care on medical and long-term care expenditures: A propensity score-matched analysis using LIFE study data. - Jun Kawabata; Haruhisa Fukuda (PLoS ONE, 2023)
Objective Japan introduced a financial incentive scheme in April 2016 to improve hospital-based dementia care, but its effectiveness remains unclear. This study aimed to investigate the scheme's impact on medical and long-term care (LTC) expenditures, as well as on changes in care needs levels and daily living independence levels among older persons one year after hospital discharge. Methods We linked medical and LTC claims databases, and retrospectively identified patients who received LTC needs certification and daily living independence assessments in Fukuoka, Japan. Case patients (received care under the new scheme) were those admitted from April 2016 to March 2018, and control patients were those admitted from April 2014 to March 2016 (before the scheme was implemented). Through propensity score matching, we identified 260 case patients and 260 control patients, and compared using t-tests, and chi-square tests. Results The analyses found no significant differences between the case and control groups in medical expenditure (US$26,685 vs US$24,823, P = 0.37), LTC expenditure (US$16,870 vs US$14,374, P = 0.08), daily living independence level changes (26.5% vs 20.4%, P = 0.12), or care needs level changes (36.9% vs 30%, P = 0.11). Conclusions The financial incentive scheme for dementia care did not demonstrate any beneficial effects on patients' healthcare expenditures or health conditions. Further studies are needed to examine the scheme's long-term effects.